Systematic Reviewers in Clinical Neurology Do Not Routinely Search Clinical Trials Registries - Sinnett, Philip Marcus; Carr, Branden; Cook, Gregory; Mucklerath, Halie; Varney, Laura; Weiher, Matt; Yerokhin, Vadim; Vassar, Matt (PLOS ONE, 2015)
We examined the use of clinical trials registries in published systematic reviews and meta-analyses from clinical neurology. A review of publications between January 1, 2008 and December 31, 2014 from five neuroscience journals (Annals of Neurology, Brain, Lancet Neurology, Neurology, and The Neuroscientist) was performed to identify eligible systematic reviews. The systematic reviews comprising the final sample were independently appraised to determine if clinical trials registries had been included as part of the search process. Studies acknowledging the use of a trials registry were further examined to determine whether trial data had been incorporated into the analysis. The initial search yielded 194 studies, of which 78 systematic reviews met the selection criteria. Of those, five acknowledged the use of a specific clinical trials registry: four reviewed unpublished trial data and two incorporated unpublished trial data into their results. Based on our sample of systematic reviews, there was no increase in the use of trials registries in systematic review searches over time. Few systematic reviews published in clinical neurology journals included data from relevant clinical trials registries.